Long-term outcomes in elderly patients with ANCA-associated vasculitis. (17th September 2019) - McGovern, Dominic; Williams, Sam P; Parsons, Katrina; Farrah, Tariq E; Gallacher, Peter J; Miller-Hodges, Eve; Kluth, David C; Hunter, Robert W; Dhaun, Neeraj
Abstract: Objective: ANCA-associated vasculitis (AAV) is a small vessel vasculitis that commonly presents in the elderly. However, there are few long-term outcome data for these patients. Here, we assessed long-term outcomes in a single-centre cohort of elderly patients with AAV. Additionally, we tested whether a pre-morbid frailty score could aid prognosis. Methods: Using a prospectively-compiled dataset, we investigated patients over the age of 65 who presented with AAV between 2005 and 2017 to a regional vasculitis centre. We used a Cox model to determine the factors associated with mortality. We also compared outcomes in pre-specified subgroups stratified by baseline frailty score, ANCA serotype and induction immunosuppression (with cyclophosphamide, rituximab or mycophenolate mofetil used as the main glucocorticoid-sparing agent). Results: 83 patients were included in the study and were followed for a median of 1203 days. Median age was 74 years (range 65–92). Two- and five-year survival in the overall cohort were 83% (95% CI 75, 92%) and 75% (95% CI 65, 86%), respectively. The median cumulative dose of oral prednisolone was 2030 mg during the first three months. Only one patient received intravenous glucocorticoids. Age, frailty score and CRP at presentation were independently associated with mortality; all deaths occurred in patients aged over 75 at presentation. Patients treated with a cyclophosphamide-based induction regimen tended to be younger than those treated with rituximab or mycophenolate mofetil. Survival was better in the cyclophosphamide-treated group. Conclusion: In the contemporary era, the overall prognosis of AAV in elderly patients is good. Baseline frailty associates with disease outcomes including mortality. A low-dose glucocorticoid regimen (avoiding intravenous methylprednisolone) can be used to treat AAV effectively in elderly patients.